The influence of changes in activity-based financing on hospital readmissions for the elderly - Jun Yin; Fredrik A. Dahl; Terje P. Hagen; Hilde Lurås (University of Oslo, 2016)
Activity-based financing of Norwegian hospitals was implemented in 1997. An earlier study shows that when the activity-based component increases, the average length of stay for the elderly is reduced. If this reduction entails premature discharge, an increased activity-based component may have the undesirable side effect of increasing readmission rates. Yearly the Norwegian government decides the size of the activity-based component, and all hospitals face the same size. In this paper, we investigate whether the level of activity-based financing is associated with the readmission rates for acute-care patients above 70 years of age. The sample consisted of 468 010 hospital admissions among elderly patients in the period from 2000 to 2007. Using repeated cross-sectional data extracted from the Norwegian Patient Registry, a Cox regression model was used to estimate factors that may influence the hazard rate of a readmission within 30 days. The overall 30-day readmission rate was 6.6%. The results demonstrate that the activity-based component had no significant effect on the readmission rate. Patient-specific factors such as age, gender, diagnoses, comorbidities, as well as the time trend, were important predictors of readmission rates. We also found a statistically significant random effect of hospitals, although this effect was less substantial than the impact of patient characteristics. Our results show that the effect of the activity-based component on the readmission rate was negligible when it varied between 40% and 60%. Published: Online May 2016. In print August 2016.